LIVE PROCESSING AND FEEDBACK ON A COMBINED LASERSCANNING AND PHOTOGRAMMETRIC DOCUMENTATION WORKFLOW - L. Stampfer (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2024)
The use of a combined terrestrial laserscanning (TLS) and structure-from-motion (SFM) surveying approach has proved to be able to deliver advantageous benefits in terms of coverage and surface rendition. The elaboration of such approaches entails a succession of processes and are without many options for on-site feedback largely dependent on the experience of the surveyor. In support of this approach a combined automated processing workflow with augmented reality feedback is introduced, allowing operators to get a better understanding of their progress and project success during surveying. To do so native TLS and SFM software is connected to a shared network and data storage environment and controlled within an active framework. Within this, scans and images are aligned within RealityCapture and resulting registration is visualised to the operator using augmented reality (AR). To achieve complete independence of pre-scanned environments, the augmented reality application presented within this research uses a GNSS supported visual SLAM algorithm. With this the application is able to position virtual objects – such as markers representing the positions of registered cameras – within a physical space using only their geoposition as reference. The workflow presented here should be understood as a proof of concept to determine possible improvements that would enable such interactive means of surveying and would allow deeper integration of components into a combined AR supported documentation workflow.